Engaging students to write procedure texts through the culturally-relevant activity of bark painting - Wigati Yektiningtyas; Ruth Naomi Nancy Wompere; Niko Kobepa; Tri Apniani Sunarsih (UNIB Press, 2023)
For most EFL students, writing in English is a boring and challenging skill; therefore, creative and attractive media such as bark painting is needed. Bark painting is one of the cultural heritages that has not been valued and recognized by Papuan young people as a culturally important medium. This study aimed at exploring the ways of engaging students to write procedure texts using bark painting and finding the importance of infusing bark painting in teaching procedure text. This descriptive-qualitative study took place in Jayapura, Papua, Indonesia, between January and March 2021. There were students of the Social Science program, 5 Senior High School teachers, 3 tribal chiefs, 3 elders, 3 bark painters, and 2 cultural practitioners involved as the participants. The data were collected by using observation, interview, and FGD (Focus Group Discussion). From the data analysis, the study found that by engaging the students in learning writing procedure text using bark painting, they could effectively and enthusiastically learn the social functions, generic structure, and linguistic features of writing procedure text with a media which is culturally close to them, and they could learn and indirectly disseminate cultural heritage as well as learn the good character of the elders.